2012
DOI: 10.1007/978-3-642-33486-3_46
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Time-Series Classification

Abstract: Abstract. Time-series classification is a field of machine learning that has attracted considerable focus during the recent decades. The large number of time-series application areas ranges from medical diagnosis up to financial econometrics. Support Vector Machines (SVMs) are reported to perform non-optimally in the domain of time series, because they suffer detecting similarities in the lack of abundant training instances. In this study we present a novel time-series transformation method which significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the context here, it can measure which model best describes a time series, without assuming that this model is where the data were originally generated from. Classification of time series has been previously used in Grabocka et al (2012) and Krzemieniewska et al (2014). It was shown in Yau and Davis (2012) that the autocorrelation function and periodogram of data generated from a changepoint model and a long memory model exhibit similar structures (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the context here, it can measure which model best describes a time series, without assuming that this model is where the data were originally generated from. Classification of time series has been previously used in Grabocka et al (2012) and Krzemieniewska et al (2014). It was shown in Yau and Davis (2012) that the autocorrelation function and periodogram of data generated from a changepoint model and a long memory model exhibit similar structures (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The downside to using shapelets is the time complexity. The heuristic techniques described in recent research [15,6] offer potential speed up (often at the cost of extra memory) but are essentially different algorithms that are only really analogous to shapelets described in the original research [17]. Our interest is in optimizing the original shapelet finding algorithm within the context of the shapelet transform.…”
Section: Resultsmentioning
confidence: 99%
“…The approximate techniques include reducing the dimensionality of the candidates and using a hash table to filter [15], searching the space of shapelet values (rather than taking the values from the train set series) [6] and randomly sampling the candidate shapelets [4]. Our focus is on improving the accuracy and speed of the full search.…”
Section: Shapelet Based Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the outlined data/domain specific challenges, this paper will attempt to develop a feature space extraction methodology that will construct an analysis of stellar variables and characterize the shape of the periodic stellar variable signature. A number of methods have been demonstrated that fit this profile [21,18,19], however many of these methods focus on identifying a specific time series shape sequence in a long(er) continuous time series, and not necessarily on the differentiation between time series sequences. To address these domain specific challenges, the following methodology outline is implemented:…”
Section: Proposed Feature Extraction Methodologymentioning
confidence: 99%